Pengaruh Birthing Ball Terhadap Lama Kala I Fase Aktif Pada Primigravida Di Pmb Yulis Indriana, Malang - Gemini Astrika; Ardi Panggayuh; Tri Mardiyanti (Poltekkes Kemenkes Malang, 2019)
The duration of labour in primigravida can effect on exhausting and decrease energy phisically. Otherwise, exhausted can impact the duration of labor longer because of inefficient uterine contraction. It also can cause prolonge labour that increase the risk of haemorage postpartum. Exhausted in labour can be avoided by speed up the duration of labour using birthing ball. This study aimed to identify the effect of birthing ball on the duration of active phase in primigravida. An observatinal analitic with cross sectional design was used. Subjects were randomly devided into intervention group and control group. In this study, subjects were selected using systematic random sampling and quota sampling that was conducted on 20 subjects according to the inclusion criteria. The datas were collected using identity sheet, observation sheet, and partograph. Then, the datas were analyzed using Chi Square Test with significance level T approximately same as 0.05. According to the analyze result that has gotten, p value 0,045 is smaller than T approximately 0,05, so H0 is rejected which means there is an effect of birthing ball on the duration of active phase in primigravida. Considering the effect of birthing ball on the duration of active phase in primigravida, performing birthing ball is recommended as a useful strategy to help speed up the duration of active phase in primigravida.